Pemanfaatan Pupuk Kandang Sapi dan Pupuk Organik Cair Kulit Pisang Untuk Meningkatkan Pertumbuhan dan Produksi Tanaman Jagung Manis (Zea mays L. saccharata Sturt) - Daniel Steven Tumanggor; Nuraida Nuraida; Ahmad Sofian (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Al Azhar Medan, 2024)
Sweet corn (Zea mays L. saccharata Sturt) is one type of annual crop whose life cycle is only 80 - 150 days. This study aims to determine the growth and production of sweet corn (Zea mays L. saccharata Sturt) due to the application of cow manure and banana peel liquid organic fertilizer. This research was conducted from March to June 2023. This study used a Factorial Randomized Group Design with 2 factors studied and 3 replications where the first factor was cow manure (K) consisting of 3 levels, namely K0 = 0 tons ha-1 (control), K1 = 15 tons ha-1, K2 = 30 tons ha-1. The second factor is banana peel liquid organic fertilizer (P) which consists of 4 levels, namely P0 = 0% (control), P1 = 10% liter-1 of water, P2 = 20% liter-1 of water, P3 = 30% liter-1 of water. The results showed that the application of cow manure had a very significant effect on the parameters of plant height, leaf area, cob length, cob diameter and cob weight per sample and had a significant effect on the cob weight parameter per plot. The application of banana peel liquid organic fertilizer has a significant effect on the cob diameter parameter, but has no significant effect on the parameters of plant height, leaf area, cob length, cob weight per sample and cob weight per plot. While the interaction between cow manure and banana peel liquid organic fertilizer had no significant effect on all parameters observed.